Supply Chain Online Shop In Covid 19 Pandemic (Netnography: Instagram Nagishop) - Bellina Reggita; Diah Yuliastri Diah Yuliastri; Firna Septyaningrum; Sigit Hermawan (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2020)
During the Covid 19 pandemic not only impacted health, but also economic and humanitarian aspects. The shift in the value of people's needs during the pandemic caused several economic sectors to struggle hard to survive. One of the businesses that still looks promising today is an online shop, where in an online shop there is no need for face-to-face and physical contact between sellers and buyers which is in accordance with government recommendations during the Covid 19 pandemic to keep physical distancing and staying at home. One onlineshop that has a large enough follower istagram is Nagisshop, where this onlineshop has a special strategy to keep sales and consumers to remain loyal. The uniqueness that is in Nagisshop makes this online shop has increased buyer and follower istagram compared to the previous year. The increase in buyers in 2020 reached more than 300% per day compared to 2019. By utilizing the supply chain that had been built before, Nagisshop expanded its wings and promotion on other social media. Previous supply chain components are sellers, importers, resellers, consumers (end users).